IoT-based smart cat home with sensor integration and B lynk application for real-time monitoring of cat temperature, feed, and activity - Sintawati, Andini; Tambunan, Alda Emly (Privietlab, 2026)
Cats are one of the most popular pets in Indonesia, especially purebred cats that require special care, including temperature control, lighting, and food and water availability. Cat owners often face challenges when leaving their pets for extended periods, necessitating an effective monitoring system for their pets. This study aimed to design and implement an Internet of Things (IoT)-based Smart Cat Home system to monitor and control cage conditions in real time. The system uses ESP32 and ESP32-CAM microcontrollers, DHT22 sensors for temperature and humidity, LDR sensors for lighting, Load Cell sensors for food and water, and the Blynk application as a remote monitoring medium. The research methods included requirements analysis, hardware and software design, sensor integration, and functional testing. The test results show that the system works in automatic mode with a 95% success rate and responds quickly to commands. The developed Smart Cat Home system has been proven to work well and reliably to help cat owners monitor cage conditions efficiently and remotely.